Seasonality of calliphorid and sarcophagid flies across Canterbury arable farms requiring pollinators - Howlett, B.G.; Davidson, M.M.; Pattemore, D.E.; Walker, M.K.; Nelson, W.R. (New Zealand Plant Protection, 2016)
Calliphorid and sarcophagid flies are common widespread pollinators of vegetable and forage seed crops Information regarding their seasonal occurrence on arable farms growing these crops may help predict their temporal effectiveness and flexibility as pollinators Window intercept traps (12 per farm) were placed at the edges of crop paddocks across five arable farms in Canterbury for periods of 16 weeks from 2012 to 2015 Total trapping days for each season over the four years were summer 128 autumn 92 winter 199 and spring 35 Flies from at least six species were commonly caught from spring to autumn Mean farm insect counts found Calliphora vicina to be the most abundant species in spring (2373) summer (891) and winter (32) while Oxysarcodexia varia (2129) and Pollenia spp (1903) were most abundant in autumn Their broad temporal abundance shows their potential to pollinate crops that flower at different times